2022
DOI: 10.1016/j.cllc.2021.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer Stage Shift as a Result of COVID-19 Lockdowns in New York City, a Brief Report

Abstract: Introduction : The COVID-19 pandemic reached New York City in early March 2020 resulting in an 11-week lockdown period to mitigate further spread. It has been well documented that cancer care was drastically affected as a result. Given New York City's early involvement, we attempted to identify any stage shift that may have occurred in the diagnoses of non-small cell lung cancer (NSCLC) at our institution as a result of these lockdowns. Methods : We conducted a retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…This descriptive analysis suggests an immediate negative impact on lung cancer diagnoses of COVID-19 restrictions, with a sharp decrease in early stage diagnoses when a “pause” on elective procedures was introduced during the Spring of 2020, as well as when COVID-19 cases sharply increased during the Winter of 2021. Although a lot have been said on the delays in diagnosis and treatment following the COVID-19 pandemic ( 3 - 5 ), few studies have shown how delays affect stage at diagnosis ( 6 ), and those who studied the problem did not apply the sophisticated approach we used. The pandemic affected screening, early detection, and drastically reduced any patient’s contact with the health system that would have prompted an early lung cancer diagnosis.…”
mentioning
confidence: 99%
“…This descriptive analysis suggests an immediate negative impact on lung cancer diagnoses of COVID-19 restrictions, with a sharp decrease in early stage diagnoses when a “pause” on elective procedures was introduced during the Spring of 2020, as well as when COVID-19 cases sharply increased during the Winter of 2021. Although a lot have been said on the delays in diagnosis and treatment following the COVID-19 pandemic ( 3 - 5 ), few studies have shown how delays affect stage at diagnosis ( 6 ), and those who studied the problem did not apply the sophisticated approach we used. The pandemic affected screening, early detection, and drastically reduced any patient’s contact with the health system that would have prompted an early lung cancer diagnosis.…”
mentioning
confidence: 99%
“…By investigating the stage distribution of lung cancer in 554 patients between 1 July 2019 and 31 March 2021, a retrospective study at a large hospital in New York found that, in comparison with the distribution in nonpandemic months and the second quarter of 2020, which included the lockdown period, the proportion of stage IV cancers diagnosed during the quarters succeeding gradual resumption (October 2020 to March 2021) increased significantly. 35 Arguably, an apparent stage‐shift was a consequence of lockdown‐related delays and the reported exponential nature of lung cancer growth and time to progression. Interestingly, a recent study analyzing circulating concentrations of tumor DNA in newly diagnosed metastatic colorectal cancer before vs after lockdown in France found that patients diagnosed after it had a greater tumor burden (defined as statistically higher concentrations of tumor DNA) than those diagnosed before, and that the median survival of patients with high tumor DNA concentrations was lower than of those with lower concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence exists on stage‐shift to later‐stage disease due to the pandemic. By investigating the stage distribution of lung cancer in 554 patients between 1 July 2019 and 31 March 2021, a retrospective study at a large hospital in New York found that, in comparison with the distribution in nonpandemic months and the second quarter of 2020, which included the lockdown period, the proportion of stage IV cancers diagnosed during the quarters succeeding gradual resumption (October 2020 to March 2021) increased significantly 35 . Arguably, an apparent stage‐shift was a consequence of lockdown‐related delays and the reported exponential nature of lung cancer growth and time to progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the lockdown in Shanghai, cancer patients were allowed to have a caregiver accompany them at the emergency department and the bedside during hospitalization. There is increasing evidence about the challenges of accessing health care services during the lockdown ( Topriceanu et al, 2021 ; Mynard et al, 2022 ). Yet, what is unclear is how family caregivers navigate the pre-hospital admissions process aimd strict pandemic control measures and supportive policies for cancer care.…”
Section: Introductionmentioning
confidence: 99%